Public self-consciousness moderates the link between displacement behaviour and experience of stress in women - Mohiyeddini, Changiz; Bauer, Stephanie; Semple, Stuart (Stress, 2013)
When stressed, people typically show elevated rates of displacement behaviour - activities such as scratching and face touching that seem irrelevant to the ongoing situation. Growing evidence indicates that displacement behaviour may play a role in regulating stress levels, and thus may represent an important component of the coping response. Recently, we found evidence that this stress-regulating effect of displacement behaviour is found in men but not in women. This sex difference may result from women's higher levels of public self-consciousness, which could inhibit expression of displacement behaviour due to the fear of projecting an inappropriate image. Here, we explored the link between public self-consciousness, displacement behaviour and stress among 62 healthy women (mean age = 26.59 years; SD = 3.61). We first assessed participants' public self-consciousness, and then quantified displacement behaviour, heart rate and cognitive performance during a Trier Social Stress Test (TSST) and used self-report questionnaires to assess the experience of stress afterwards. Public self-consciousness was negatively correlated with rate of displacement behaviour, and positively correlated with both the subjective experience of stress post-TSST and the number of mistakes in the cognitive task. Moderation analyses revealed that for women high in public self-consciousness, high levels of displacement behaviour were associated with higher reported levels of stress and poorer cognitive performance. For women low in public self-consciousness, stress levels and cognitive performance were unrelated to displacement behaviour. Our findings indicate that public self-consciousness is associated with both the expression of displacement behaviour and how such behaviour mediates responses to social stress.
Gesehen am 25.05.2021